RETRANSLATION OF CULTURAL CODE IN RUSSIAN-PORTUGUESE LITERARY TRANSLATION: TRANSLATION EXPERIMENT - Vasilisa A. Danilova (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie)
The article questions adequacy of retranslation the cultural code in literary text when translated from Russian to Portuguese. The aim of the study is to develop the concept of translation experiment, which allows of identifying adequate ways of relaying realia in the Russian-Portuguese literary translation. The research material consists of translations into Portuguese of A.S. Pushkin’s novel Eugene Onegin carried out by D. Alves, N. and F. Guerra. Some inaccurate translation decisions made whilst transferring realia into Portuguese were identified: choosing incorrect translation equivalents, using loan translation, transcription and transliteration of Russian realia without any remarks. The study revealed that implementation of these incorrect translation solutions results in neutralization of national cultural flavour, omission of denotative and/or connotative meaning, provoking ambiguity in culturally-marked units comprehension. The concept of the translation experiment with native Portuguese speakers was proposed to determine adequate ways of translating such groups of realia as domestic, ethnographic, natural, onomastic and phraseological. The results of the experiment revealed that adequacy in the translation of all thematic groups of realia, except for phraseological units, is observed in correlation and calquing. The correlation allows and calquing, which allow the translator to preserve the national and cultural flavour of realia, convey their meanings and recreate the original communicative effect in the translation text. As for phraseological units, the adequate method of translation is the phraseological equivalent, which also ensures the transfer of semantics and national-and-cultural specifics of the analyzed units in Portuguese translations.